Pengaruh Penerapan Smart Wifi Plug untuk Optimalisasi Lampu Penerangan Jalan Di Bekasi - syadiyah, kholifahtul; Adinda Sangadji, Silvany; S.P Silitonga, Gerson; Fikri Fahmi, Muhammad; Naufal Adlin, Muhammad; Azra Thufeil, Muhammad; Ahyar, Muhtadin; Chekas Arya, Socha; Rama Insiyanda, Dita (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Public street lighting (PJU) is essential for road user safety and comfort, yet often inefficient, leading to energy waste and high operational costs due to a lack of optimal control. This community service research introduces the Smart WiFi Plug, an Internet of Things (IoT)-based device, as an innovative solution for optimizing energy consumption in PJU systems. The Smart WiFi Plug enables automatic and remote control of electricity via smartphone applications, allowing adjustment of operational times and light brightness according to needs or environmental conditions.Employing a quantitative approach, data were collected through direct observation and power consumption measurements before and after implementation at PJU points47. The results indicate a significant energy consumption reduction, reaching 30% to 40%. This decrease in electricity consumption directly implies an average operational cost efficiency of 35%. The Smart WiFi Plug also enhances flexibility in street light control, enabling remote management and adaptation to various conditions without manual intervention. This optimization delivers positive economic impacts for local governments and contributes to sustainability and environmental friendliness by reducing carbon emissions. Although challenges such as limited network infrastructure persist, this solution holds significant potential for integration into smart city development, supporting smarter, energy-efficient, and adaptive street lighting systems.